Machine Learning Approach for Predicting Appointment No-Show in Healthcare - Khalouf, Dana (2024)
A Master of Science thesis in Engineering Systems Management by Dana Khalouf entitled, “A Machine Learning Approach for Predicting Appointment No-Show in Healthcare”, submitted in July 2024. Thesis advisor is Dr. Abdulrahim Shamayleh and thesis co-advisors are Dr. Hussam Alshariedeh and Dr. Mahmoud Awad. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).